Theoretical Investigation of Waste Heat Recovery from an IC Engine Using Vapor Absorption Refrigeration System and Thermoelectric Converter. Issue 6 (4th April 2014) - Sonthalia, Ankit; Reddy, Somesh; Kumar, C. Ramesh; Kamani, Keval
<x xml:space="preserve">Abstract</x> This study proposes the preliminary simulation of a single cylinder spark ignition engine with waste heat recovery system. To harvest waste heat energy from the engine exhaust a thermoelectric generator coupled to a vapor absorption refrigeration (VAR) system was proposed in this simulation work. Parametric simulation of engine, thermoelectric generator and VAR using thermodynamic relations was carried out in MATLAB – Simulink software. An attempt has been made mathematically to integrate engine, thermoelectric generator and VAR system to study the effect of engine load, speed, equivalence ratio on thermoelectric output and coefficient of performance (COP) of a VAR system. In this study, the VAR system runs by taking heat energy from the exhaust gas and the electric power produced by a thermoelectric generator was utilized to run the pump of the refrigeration system. It was found that COP of the absorption refrigeration system depends on engine load, speed and air fuel equivalence ratio. The study also reveals that about 10% to 15% of the total exhaust energy can be harvested using this system.